An experimental study on the application of oxygenated fuel to diesel engines. (15th July 2019) - Yeom, Jeong-Kuk; Jung, Suk-Ho; Yoon, Jeong-Hwan
Abstract: This paper deals with the evaporative characteristics and engine test results of emulsified fuels composed of diesel and hydrogen peroxide to reduce engine emissions by means of fuel design. The purpose of this study is basic research for applying emulsified fuel (EF) to engine through investigating the change of properties of emulsified fuel and the analysis of the behavior characteristics of free and impinging spray. In addition, the results are applied to real engine and the results of the study are presented comprehensively. To make the emulsified fuel for the experiment, the surfactant for mixing the emulsified fuel was fixed at a mixing ratio of 3% (vol.) of the total volume of the fuel, and Span 80 and Tween 80 were mixed at a ratio of 9:1. The mixing ratio of the hydrogen peroxide of the emulsified fuels was set to increase by 10% from EF2 to EF42 in consideration of the amount of the surfactant, and expressed as EF0 (diesel) in the case of diesel only. However, for the stable operation of the engine, the actual engine experiment was conducted only for the mixing ratios of EF0 and EF2. In order to analyze the characteristics of evaporation and engine emission reduction according to the mixing ratio of emulsified fuel, the experiments of droplet, free spray, impinging spray and actual engine were performed, respectively. Experimental images for visualization were obtained by using scattered light and Schlieren method. In the case of the droplet experiment, the evaporation characteristics were analyzed by free drop of the fuel droplet on a heating plate maintained at 473 K. The injection pressures of the emulsified fuel were set to 40 MPa, 60 MPa, 80 MPa and 100 MPa. In the case of free spray, experiment was carried out in a constant volume chamber maintained at room temperature (288 K) and 423 K. In the case of the impinging spray, the temperature of the impinged plate was changed to 423 K, 473 K and 523 K, respectively. The evaporation characteristics of the emulsified fuel were analyzed through the analysis of the fuel diffusion area and the entropy analysis based on statistical thermodynamics using the results obtained from such experiments. It was found that droplet and spray evaporation were promoted as the mixing of hydrogen peroxide in the emulsified fuel increased, and a method of quantitatively analyzing the experimental phenomenon could be proposed. From these results, it can be expected that the mixture of emulsified fuel mixed with hydrogen peroxide can be formed faster than the conventional diesel when applied to a real diesel engine. As a result, it is expected to play a positive role in terms of engine emission reduction. Based on these basic experimental results, emulsified fuels with mixing ratios of EF0 and EF2 were applied to diesel engine and actual engine test was conducted. NOx and soot were reduced by rapid mixture formation due to the fuel evaporation promoting effect as well as the effect of lowering the temperature of the combustion chamber due to the latent heat of evaporation of the hydrogen peroxide contained in the emulsified fuel. Finally, it can be confirmed that when the proper mixture ratio of emulsified fuel is selected for main engine operation, simultaneous reduction of NOx and soot is possible.